THE IMPORTANCE OF UTILIZING DIGITAL TECHNOLOGIES IN ENGLISH LANGUAGE INSTRUCTION - Kaldykulova M. Zh. (Scientific Research and Experimental Development, 2025)
This study investigates the significance and evolving role of digital technologies in English language instruction through a comprehensive bibliometric analysis of Scopus-indexed literature from 2000 to 2025. Drawing on quantitative and qualitative data, the research identifies key thematic trends, geographic patterns, and influential publications that have shaped the discourse on technology-enhanced language learning. The findings highlight a shift from traditional instructional models toward more learner-centered, multimodal, and digitally integrated pedagogies. Notably, the study reveals three dominant conceptual clusters: pedagogical integration, technological tools and multimodality, and learner-centric approaches. While the integration of digital technologies offers clear pedagogical advantages such as increased learner autonomy, engagement, and accessibility it also presents ongoing challenges, particularly concerning teacher training, digital literacy, and equitable access. The study concludes that successful implementation depends on systemic readiness, pedagogical innovation, and context-sensitive strategies. It contributes to the global discourse on educational technology by offering insights into emerging research gaps and future directions for policy, practice, and inquiry